A experiência estética do espetador face à utilização da Realidade Virtual nas obras de Arte Multimédia : caso de estudo: as obras de Janet Cardiff e George Bures Miller - Wendhausen, Maria (2024)
The evolution of the role of images and their impact on Western society from modernity to postmodernity is undeniable. This dissertation analyses the aesthetic experience of the spectator in the face of multimedia artworks that use the resource of virtual reality during the transition to the digital age in the West. To this end, theories that contextualize and substantiate this phenomenon will be addressed, examining the historical background that led to the growing interest shown by artists in immersive strategies and the use of virtual reality as an expressive medium. The artists Janet Cardiff and George Bures Miller are considered particularly relevant to this research, whose work will be analyzed in the case study in relation to the juxtaposition of realities proposed by their artworks. In this sense, an investigative path is outlined that has as its starting point the analysis of the ontological foundations of the image and the ecological approach to perceptual systems, aiming to deepen the understanding of the aesthetic conception of space by the spectator. Since, it seeks to explore virtual reality as a space of multiple possibilities, which aims to deceive the viewer's perception through immersion. To this purpose, some examples of spaces of illusion and immersion will be examined, to understand the increasing use of virtual reality under the scope of technological operationalization. Therefore, it explores the evolution of the production of virtual images, from the capture of time, from the emergence of photography to the overcoming of staticity by the cinematographic medium and the inevitable integration of artistic forms seen in the late 20th century. Based on this trajectory of study, the dissertation then focuses on the work of Janet Cardiff and George Bures Miller, with the aim of understanding virtual reality and reality as intrinsically related manifestations, which, in short, present themselves as twin phenomena of the same principle.